Monoamine oxidase A: An emerging therapeutic target in prostate cancer - Chen, Chia-Hui; Wu, Boyang Jason (Frontiers in Oncology, 2023)
Monoamine oxidase A (MAOA), a mitochondrial enzyme degrading biogenic and dietary amines, has been studied in the contexts of neuropsychiatry and neurological disorders for decades, but its importance in oncology, as best exemplified in prostate cancer (PC) to date, was only realized recently. PC is the most commonly diagnosed non-skin cancer and the second deadliest malignancy for men in the United States. In PC, the increased expression level of MAOA is correlated with dedifferentiated tissue microarchitecture and a worse prognosis. A wealth of literature has demonstrated that MAOA promotes growth, metastasis, stemness and therapy resistance in PC, mainly by increasing oxidative stress, augmenting hypoxia, inducing epithelial-to-mesenchymal transition, and activating the downstream principal transcription factor Twist1-dictated multiple context-dependent signaling cascades. Cancer-cell-derived MAOA also enables cancer-stromal cell interaction involving bone stromal cells and nerve cells by secretion of Hedgehog and class 3 semaphorin molecules respectively to modulate the tumor microenvironment in favor of invasion and metastasis. Further, MAOA in prostate stromal cells promotes PC tumorigenesis and stemness. Current studies suggest that MAOA functions in PC in both cell autonomous and non-autonomous manners. Importantly, clinically available monoamine oxidase inhibitors have shown promising results against PC in preclinical models and clinical trials, providing a great opportunity to repurpose them as a PC therapy. Here, we summarize recent advances in our understanding of MAOA roles and mechanisms in PC, present several MAOA-targeted strategies that have been nominated for treating PC, and discuss the unknowns of MAOA function and targeting in PC for future exploration.